PEMERIKSAAN CEMARAN Escherichia coli, Shigella sp DAN Salmonella sp PADA SUSU SAPI PERAH YANG DIPEROLEH DARI PETERNAKAN ASAM KUMBANG KECAMATAN MEDAN SELAYANG - Zuhairiah, Zuhairiah; Maimunah, Siti; Silitonga, Maringan (UNIVERSITAS SARI MUTIARA INDONESIA, 2021)
Milk is a drink that is mandatory for consumption by the public, especially for children, therefore, milk must be free from contamination with Escherichia coli, Shigella sp and Salmonella sp bacteria, through the tools used are not clean, the environment is dirty, the hands of workers, and others. This study aims to determine the presence or absence of Escherichia coli, Shigella sp, and Salmonella sp bacteria in Dairy Cow Milk obtained from the Asam Kumbang Farm, Medan Selayang District. The research sample was ten samples of milk from dairy cows in one farm with different cows which were treated with two aseptic and non-aseptic treatments. The research method used is descriptive research with MPN (Most Probable Number) method to count coliform bacteria followed by an examination of LB, BGLB, EMBA media, gram staining, biochemical tests, IMVIC tests, and user testing methods on samples of Shigella sp and Salmonella bacteria sp followed by an examination of NB, SCB, SSA media, gram staining, biochemical tests, and IMVIC. The results showed that one aseptic sample A and 3 non-aseptic samples A, B, C had Escherichia coli bacteria in dairy cows' milk. The quality of milk must comply with the requirements of SNI 3141.1:2011 Fresh Milk Quality and the Maximum Limit of Microbial Contamination in SNI 7388-2009 Fresh Milk.